2015
DOI: 10.1016/j.memsci.2014.09.048
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of N and H atoms adsorption and NH formation on Pd(111) and Pd3Ag(111) surfaces

Abstract: The role of the presence of Ag atom in Pd 3 Ag(111) surface on the adsorption of N and H atoms and NH species was studied by using first-principles calculations based on density functional theory (DFT). The adsorption energies of N and NH species are weakened by at least 0.50 eV when Ag atom is one of the nearest neighbors, in contrast to the case of H, in which the adsorption energies are weakened by at most 0.15 eV. Local density of states (LDOS) profiles show that for N and NH adsorption near the silver all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Our focus is on the Volmer process of HOR catalysis in alkaline medium and that is studied by hydrogen adsorption and using water formation on the FCC site of the Pd(1 1 1) metallic surface. The recent DFT calculations as well as experimental findings also suggest that the most favorable surface site for atomic/molecular group adsorption on the Pd(1 1 1) surface is the FCC site in comparison to the other surface sites; HCP, ONTOP and BRIDGE sites [37][38][39][40]. Although, the actual interaction of the hydrogen atom with the mixed electronic states of palladium metal is still unclear but due to a large electro-negativity difference of H and Pd-surface, the H atom seems to preserve its protonic character on the palladium surface [41].…”
Section: Introductionmentioning
confidence: 95%
“…Our focus is on the Volmer process of HOR catalysis in alkaline medium and that is studied by hydrogen adsorption and using water formation on the FCC site of the Pd(1 1 1) metallic surface. The recent DFT calculations as well as experimental findings also suggest that the most favorable surface site for atomic/molecular group adsorption on the Pd(1 1 1) surface is the FCC site in comparison to the other surface sites; HCP, ONTOP and BRIDGE sites [37][38][39][40]. Although, the actual interaction of the hydrogen atom with the mixed electronic states of palladium metal is still unclear but due to a large electro-negativity difference of H and Pd-surface, the H atom seems to preserve its protonic character on the palladium surface [41].…”
Section: Introductionmentioning
confidence: 95%
“…This condition caused the flux of hydrogen passing through the membrane wall and its association to form H 2 became lower, leading to low hydrogen recovery. The mechanism of N(ads) effect on H 2 permeation had also been studied previously by Chantaramolee et al [21]. In addition, at low flow rates the formation of film coating on the membrane surface would be greater [39,52].…”
Section: Start-up Behavior With Dynamic Feed Gas Flowratementioning
confidence: 61%
“…However, the Pd membrane has a major drawback related to the high price of the Pd material [20]. Moreover, even though the pure Pd metal has a high level of hydrogen permeation, it suffers from embrittlement at temperatures below 300 C [21]. Therefore, the use of Pd-alloy membranes has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However, upon returning to a hydrogen rich atmosphere, it appears that most, if not all, of these adsorbed species desorb so rapidly that no noticeable hydrogen flux reduction is measured. The finding that H adsorption energies are reduced when N(ads) is present on the surface for Pd(111) [26] is likely due to conditions not relevant to permeation measurements, as it is not explained how the adsorbates are formed in the first place.…”
Section: Pure Gas Experimentsmentioning
confidence: 99%
“…Basing their work on the studies of Wang et al [21] on nitrogen inhibition of hydrogen permeance, Chantaramolee et al [26] carried out density functional theory (DFT) calculations on N and H adsorption on palladium and suggested that N(ads) lowers the adsorption energy of H(ads) on nearby sites. However, the group did not discuss the potential for N(ads) formation in the first place.…”
Section: Introductionmentioning
confidence: 99%